2019
DOI: 10.3390/molecules24234321
|View full text |Cite
|
Sign up to set email alerts
|

Antimicrobial Activity of Chamomile Essential Oil: Effect of Different Formulations

Abstract: Essential oils (EOs) are highly lipophilic, which makes the measurement of their biological action difficult in an aqueous environment. We formulated a Pickering nanoemulsion of chamomile EO (CPe). Surface-modified Stöber silica nanoparticles (20 nm) were prepared and used as a stabilizing agent of CPe. The antimicrobial activity of CPe was compared with that of emulsion stabilized with Tween 80 (CT80) and ethanolic solution (CEt). The antimicrobial effects were assessed by their minimum inhibitory concentrati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
47
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 48 publications
(53 citation statements)
references
References 38 publications
(60 reference statements)
1
47
0
1
Order By: Relevance
“…Other nanoparticles, such as ferric oxide (Fe 2 O 3 ) nanoparticles, were reported to have a stronger antifungal activity against the Cladosporium herbarium, which was marked by ROS generation [ 42 ]. A previous study showed that the ethanolic extract of Matricaria chamomilla L. has a good inhibition effect on the growth of Candida albicans and Candida tropicalis because of the lipophilic essential oils rich in flavonoid and apigenin, which are known for their antifungal properties [ 43 ]. It can be concluded that AgNPs constitute an effective antimicrobial agent against common pathogenic microorganisms.…”
Section: Resultsmentioning
confidence: 99%
“…Other nanoparticles, such as ferric oxide (Fe 2 O 3 ) nanoparticles, were reported to have a stronger antifungal activity against the Cladosporium herbarium, which was marked by ROS generation [ 42 ]. A previous study showed that the ethanolic extract of Matricaria chamomilla L. has a good inhibition effect on the growth of Candida albicans and Candida tropicalis because of the lipophilic essential oils rich in flavonoid and apigenin, which are known for their antifungal properties [ 43 ]. It can be concluded that AgNPs constitute an effective antimicrobial agent against common pathogenic microorganisms.…”
Section: Resultsmentioning
confidence: 99%
“…By gathering the great outcome of nanotechnology and the therapeutic implications of plant-derived compounds, new pharmaceutical formulations were lately developed and thoroughly evaluated. Therefore, an impressive extension of the medicinal use of phytochemicals was reported, including unconventional antioxidants [ 40 , 41 , 42 , 43 , 44 ] and antimicrobials [ 45 , 46 , 47 , 48 ], wound dressings [ 49 , 50 , 51 ], dermal products [ 52 , 53 , 54 , 55 ] and anti-cancer platforms [ 56 , 57 , 58 , 59 ].…”
Section: Introductionmentioning
confidence: 99%
“…Bu nanoemulsiua olishda stabilizator tvin-80 va etanol ishlatilgan. Nanoemulsiya Candida turidagi mikroblarni oꞌsishini toxtatishi va antioksidantlik xususiyatga egaligi oꞌrganilgan [6][7]. Dorivor oꞌsimliklar asosida moyli ekstraktlar olish juda muhim texnologik jarayon hisoblanib, u soddaligi, oson amalga oshirish mumkinligi va samaradorligi bilan ajralib turadi.…”
Section: Kirishunclassified